Reverse Microemulsion of Igepal CO-720 System as Microreactor For CdS Synthesis - Fitria Rahmawati; Indah Rizki Fitriani; Abu Masykur (ALCHEMY Jurnal Penelitian Kimia, 2014)
A Research on CdS synthesis in reverse microemulsion of Igepal CO-720 system has been conducted at various weight ratio of water to surfactant. Igepal CO-720 naturally forms  oil  in  water  (o/w)  emulsion  type  due  to  its  high  HLB  (Hydrophilic -Lipophilic Balance)  value.  Therefore,  in  this  research  the  Igepal  CO-720  system  was  inversed  into water  in  oil  (w/o)  system  before  it  was  used  as  microreactor  for  CdS  synthesis.  As comparison,  a  system  of  AOT  (Aerosol  OT;  sodium  bis (2-ethylhexyl)  sulfosuccinate) which  is  naturally  w/o  system  was  also  used  as  microreactor  for  CdS  synthesis.  The prepared  CdS  was  analyzed  by  X-ray  diffraction  for  crystal  identification,  scanning electron microscope for morphological analysis, UV-Vis for absorption edge determination and  photoelectrochemical  testing  for  photoactivity.  The  results  show that the  Igepal  CO -720  system can  be  inverted  into  w/o  system  and  can  be  used  as  microreactor  for  CdS synthesis. The prepared CdS is in nanosize with the average diameter of 2.517  ±  0.014 nm and  the  average  gap  energy  of  3.805  ±  0.178  eV.  The  prepared  CdS  in  Igepal  CO-720 system has less regular form in comparison with morphology of the prepared CdS in AOT system. As the ω  values decreases the particle diameter decreases, the gap energy increases and the %  IPCE increases. It indicates that high surfactant concentration allows small size micelles  formation  and  produced  smaller  CdS  particle  that  has  high  surface  area  and therefore  provide  higher  photocatalytic  activity  which  was  indicated  by  high  value  of  its % IPCE.